Worsening of coronary spasm during the perioperative period: A case report - Teragawa, Hiroki; Nishioka, Kenji; Fujii, Yuichi; Idei, Naomi; Hata, Takaki; Kurushima, Shuji; Shokawa, Tomoki; Kihara, Yasuki (World journal of cardiology, 2014)
We present the case of a 65-year-old male with vasospastic angina (VSA) whose condition worsened during the perioperative period. He had been diagnosed with VSA 10 years prior. He was treated with two types of vasodilators and had not experienced any chest symptoms for 5 years. At this juncture, he underwent surgery for relapsed maxillary sublingual carcinoma. He had taken two vasodilators one day prior to surgery. Intravenous infusion of nitroglycerin (NTG) was initiated immediately before the surgery and continued the following day. Instead of stopping NTG, a dermal isosorbide dinitrate tape was applied on post-operative day 1. Two days later, a complete atrioventricular block with pulseless electrical activity appeared. After cardiopulmonary resuscitation, emergent coronary angiography showed severe coronary spasm in both the left and right coronary arteries. Intracoronary infusion of nitroglycerin and epinephrine with percutaneous cardiopulmonary support relieved the coronary spasm. During the perioperative period, several factors can trigger coronary vasospasm, including the discontinuation of vasodilators. Thus, surgeons, anesthetists, and cardiologists should watch for coronary vasospasm during this period and for worsening coronary spasm when discontinuing vasodilators in patients at risk for VSA.